Pengaruh Learning Orientation, Knowledge Management, Talent Management sebagai Variabel Intervening terhadap Employee Performance - Nugraheni, Sekar Langit (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Human resources play a crucial role in all industries, as companies, governments, and businesses rely on them to achieve their objectives. The advancement of science and information technology enhances human resource capabilities, making it essential for companies to predict and evaluate business climate changes to respond effectively and efficiently. Besides having a responsive workforce, companies must ensure their employees possess high-quality competencies to support operational responsibilities. This study examines the influence of learning orientation and knowledge management on employee performance, with talent management as an intervening variable. The findings indicate that all proposed hypotheses have a significant positive impact. Learning orientation positively influences talent management, demonstrating its role in motivation and talent development. Knowledge management also enhances talent management by improving employees' skills and qualifications. Additionally, both learning orientation and knowledge management directly contribute to employee performance by facilitating access to knowledge and effective practices. Talent management itself significantly improves employee performance by fostering skill and knowledge development. Furthermore, learning orientation and knowledge management impact employee performance indirectly through talent management, emphasizing the importance of talent development in enhancing work effectiveness, efficiency, and motivation. These findings highlight the necessity for organizations to invest in learning orientation, knowledge management, and talent management strategies to optimize employee performance and achieve sustainable business success.